(untitled) (Politeja, 2019)
The aim of the article is to analyze the Russian economic policy in its external dimension (economic expansion), in the context of discussions about changes in the global economy held in the Russian Federation. The starting point for reflections in this respect is Sergey Glazyev’s view of the current evolution of international relations. The article contrasts the propositions of the Russian author and the strategy of activities of the Kremlin, which uses the state corporations for its external targets.